986 IMMUNOSENESCENCE PROFILES AND MULTIPLE LONG-TERM CONDITIONS IN VERY OLD ADULTS: THE NEWCASTLE 85+ STUDY. (14th June 2022) - Granic, A; Martin-Ruiz, C; Rimmer, L; Dodds, R M; Robinson, L; Spyridopoulos, I; Kirkwood, T B L; Zglinicki, T; Sayer, A A
Abstract: Introduction: Immunosenescence, a decline in immune system function, has been linked to several age-related diseases and geriatric syndromes, including cardiovascular diseases and frailty. Very old adults (aged ≥85 years) live with multiple long-term conditions (MLTC) or multimorbidity—a complex phenomenon of poor health defined by either counts (≥2 diseases), indices, or patterns. However, little is known about the relationship between immunosenescence and MLTC in this age group. We utilised baseline data from the Newcastle 85+ Study to investigate the association between previously defined immunosenescence profilesa and MLTC. Method: We used data from 703 participants who had multimorbidity and complete data for 16 chronic diseases and geriatric syndromes (i.e. analytic sample). MLTC counts were derived from the number of conditions and categorised into <median and ≥ median MLTC groups. We used the SPSS Two Step clustering with all 16 conditions to define MLTC patterns. Two immunosenescence profiles ('Senescent-like phenotype' and 'Less senescent-like phenotype') were defined previously from 13 lymphocyte compartments. We used multivariable regression analyses to investigate the association between immunosenescence profiles and MLTC counts, groups, and patterns. Results: In the analytic sample only 6.8% participants had 2 conditions, whilst 79.1% had 3–7, and 14.1% had ≥8 conditions, a median of 5, and 62.2% were in ≥median MLTC group. Three distinct MLTC patterns emerged by clustering: 'Low cardio-cerebro-metabolic diseases' (n = 209), 'High geriatric syndromes-arthritis' (n = 240), and 'Hypertensive-renal impairment' pattern, (n = 254). Having 'Senescent-like phenotype' characterised by higher frequency of CD4 and CD8 senescence-like effector memory cells and lower CD4/CD8 ratio was not significantly associated with either MLTC counts, ≥median MLTC group, or patterns compared with 'Less senescent phenotype'. Conclusion: No cross-sectional associations between immunosenescence and MLTC were found in the very old. Further studies are needed to determine whether immunosenescence drives change in MLTC counts and patterns and influences MLTC burden in late adulthood.